Purificação, caracterização e atividade biológica de lectinas do extrato de sementes de canavalia brasiliensis (feijão-bravo-do-Ceará) . - Barbosa, Paula Perazzo de Souza (2013)
Canavalia brasiliensis belongs to the family of Leguminosae and known as feijão-bravo-do-Ceará, it s a species from Americas. In Brazil it can be found in the North, Northeast, Midwest and Southeast. Many species of plant contain carbohydrate-binding proteins which are commonly called lectins or agglutinins which are distributed in virtually all living organisms. That study aimed to detect, purify and characterize physico-chemically a ConBr new lectin from extract of the seeds of C. brasiliensis and to evaluate its relationship with pathogenic bacteria and inflammatory processes. The lectin, with affinity for rabbit erythrocytes, was isolated by affinity chromatography on matrix Sephadex G-50 followed by chitin, and molecular exclusion in HPLC system. The purity and the molecular weight of the lectin were determined by SDS-PAGE. The protein was characterized as to the nature glycoprotein, the specific sugars and glycoproteins, resistance to pH, temperature, denaturing agents, reducing, oxidizing and chelating agents. The lectin on SDS-PAGE showed two bands of 25 and 45 kDa and a content of 47 μg of carbohydrates. It was specific for mannose, fructose and maltose. It was inactivated when heated to 90 °C and 100 °C for 10 minutes and at pH 5,0 and 13.0. It had reduced their activity in the presence of urea 4 and 8 M and sodium metaperiodate, and increased with β-mercaptoethanol. It s a metalloprotein which depend of Mg2+ for stabilizing its carbohydrate biding site. It didn t present activity against Bacillus subtilis ATCC 0516, Escherichia coli ATCC 10536, Pseudomonas aeruginosa ATCC 8027, P. aeruginosa ATCC 25619, Staphilococcus aureus ATCC 6538 e S. aureus ATCC 25925 and in the carrageenan-induced peritonitis model in mice, the lectin didn t have toxicity to animals and showed anti-inflammatory effect reducing the blood vessel permeability and migration of neutrophils in the peritoneum of mice.